Quality Assessment and Monitoring of Networks Using Passive Technique - Ilori, Abiola Olawale; Gbadamosi, Omoniyi Ajoke; Adeusi, Oluwafemi Clement (Review of Computer Engineering Research, 2020)
Continuous evaluation and monitoring of the network are essential for assessing the network’s performance level, and at the same time, it helps to identify and locate problems within the network. This study focuses on the general state of passive network measuring techniques, principally due to its reputation in terms of assessing and monitoring with a high level of accuracy. Olusegun Agagu University of Science and Technology Okitipupa Nigeria network was used as a real-life case study of how the network is being passively monitored and evaluated. For the study, Capsa network analyzer and a double network card splitter were used as the passive tool. Packet size, one-way delay, and packet fragmentation were metrics assessed on the University’s network. Although the capturing device was synchronized with the network, captures are quite short, with some negative values, so the clocks are not simultaneous in the process. However, passive tools were reported to assess and monitor the network’s performance efficiently and effectively.